2017
DOI: 10.1177/0963689717714098
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Relates to Chronic Behavioral and Neurological Symptoms in Military Personnel with Traumatic Brain Injuries

Abstract: Studies have shown that the presence of acute inflammation during recovery is indicative of poor outcomes after a traumatic brain injury (TBI); however, the role of chronic inflammation in predicting post-TBI-related symptoms remains poorly understood. The purpose of this study was to compare inflammatory biomarkers (tumor necrosis factor [TNF]-α, interleukin [IL]-6, and IL-10) in active duty personnel who either sustained or did not sustain a TBI. Service members were also assessed for post-traumatic stress d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 50 publications
2
61
2
Order By: Relevance
“…This may also be in alignment with previous research which noted IL-6 as the most considerable marker for inflammation [21]. Specifically, studies have shown that IL-6 is crucial in the relationship between immune system and CNS in inflammatory states [44]. Furthermore, 4 studies have demonstrated that individuals with PTSD have elevated proinflammatory cytokine levels when compared with healthy individuals who have not been exposed to any trauma [51][52][53][54].…”
Section: Roles Of Proinflammatory Cytokines In Ptsd: Il-1β Il-6 Tnfsupporting
confidence: 85%
See 1 more Smart Citation
“…This may also be in alignment with previous research which noted IL-6 as the most considerable marker for inflammation [21]. Specifically, studies have shown that IL-6 is crucial in the relationship between immune system and CNS in inflammatory states [44]. Furthermore, 4 studies have demonstrated that individuals with PTSD have elevated proinflammatory cytokine levels when compared with healthy individuals who have not been exposed to any trauma [51][52][53][54].…”
Section: Roles Of Proinflammatory Cytokines In Ptsd: Il-1β Il-6 Tnfsupporting
confidence: 85%
“…Through the current literature selection, studies have demonstrated that individuals with PTSD have significantly elevated serum levels of proinflammatory cytokines than the respective control group without PTSD. Specifically, individuals with PTSD demonstrated as having higher levels of serum IL-1β [15,25], IL-6 [15,16,25,[41][42][43][44][45][46][47], TNF-α [15,16,25,[42][43][44][46][47][48], IFN-γ [15,47,49], and CRP [42,50] than individuals who have been exposed to trauma but have never developed PTSD. In the current review, IL-6 demonstrated to be the most documented proinflammatory cytokine in human models of PTSD, and the majority of studies demonstrated increased IL-6 levels in the serum sample of individuals diagnosed with PTSD as compared with their respective control group.…”
Section: Roles Of Proinflammatory Cytokines In Ptsd: Il-1β Il-6 Tnfmentioning
confidence: 99%
“…However, a small percentage of individuals report symptoms many months or years postinjury; these are often the result of a variety of non–brain injury–related factors and comorbidities that are commonly found pre‐ and postinjury (Iverson, Silverberg, Lange, & Zasler, ; McCrae, ). For military personnel, one of the most common and potentially debilitating comorbidities that occurs with mTBI is posttraumatic stress disorder (PTSD; Gates et al., ), which has been shown to increase the risk of neurocognitive and neurobehavioral deficits (Stricker et al., ), suicidality (Lemaire & Graham, ), and neuronal inflammation (Devoto et al., ). When PTSD occurs concurrently with mTBI, there may be additional psychological and/or neurobiological complications that are not attributable to brain insult alone.…”
mentioning
confidence: 99%
“…E-mail: cassie.pattinson@nih.gov C 2019 International Society for Traumatic Stress Studies. View this article online at wileyonlinelibrary.com DOI: 10.1002/jts.22418 the risk of neurocognitive and neurobehavioral deficits (Stricker et al, 2017), suicidality (Lemaire & Graham, 2011), and neuronal inflammation (Devoto et al, 2017). When PTSD occurs concurrently with mTBI, there may be additional psychological and/or neurobiological complications that are not attributable to brain insult alone.…”
mentioning
confidence: 99%
“… for further cohort details). This disparity in cohort size between the case and control groups is common in human studies involving TBI . Four of the case subjects did not meet the eligibility criteria during the screening eye examination and were not retained for the testing session.…”
Section: Resultsmentioning
confidence: 99%